Comparative Study of Fish Yields with Plant Protein Sources and Fish Meal - Tuladhar, Babita (Our Nature, 2006)
Two iso-nitrogenous and iso-caloric diets were formulated using Azolla, Soya bean and oilcakes as a sole protein source in diet B and fishmeal as sole protein in diet A. Six ponds were used as experimental ponds. The fishes of three ponds were supplied with Azolla diet B while the fishes of other three ponds were supplied with fish meal diet A. Growth of the fish in three ponds with plant protein sources was significant than in the fishes of other ponds with fish meal diet A. The yield of fish supplemented with Azolla, Soya beans and Oilcakes was higher than that of fish supplied with fishmeal diet. Keyword: Plant protein, fish meal doi:10.3126/on.v1i1.300 Our Nature (2003) 1: 26-29